THE NATURE OF THE RELATIONSHIP BETWEEN SOME HEALTH INDICATORS IN INFANTS (World Bulletin of Public Health, 2022)
Rehabilitation measures in such children are carried out according to standard schemes; there is no data on the prenosological diagnosis of changes, on the peculiarities of the course of nosological forms and their correction. This approach leads to an aggravation of the morbidity of these children and to the disability of adults, determining the social and economic costs. The aim of the study was to assess the relationship between health indicators in infants born with mild intrauterine hypo plastic type development delay, compared with infants born without ASD, and with practically healthy infants from practically healthy mothers
Keywords: infants; socio-psychological adaptation; relaxation ability; measures